2015
DOI: 10.9778/cmajo.20140089
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in outcomes of methadone maintenance treatment for opioid use disorder: a systematic reviewand meta-analysis

Abstract: Sex differences were evident in polysubstance use, legal involvement and employment status among men and women receiving methadone treatment for opioid use disorders. Although the quality of evidence was low, our review highlights the need for improved implementation of sex-specific treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…The risk of bias of each included study was evaluated using an adapted version of the Newcastle-Ottawa Scale (NOS) 44. This adapted version includes four domains of risk of bias assessment: methods for selecting study participants (selection bias), methods to control for confounding (performance bias), statistical methods (detection bias) and methods of exposure and outcome assessment (information bias).…”
Section: Methodsmentioning
confidence: 99%
“…The risk of bias of each included study was evaluated using an adapted version of the Newcastle-Ottawa Scale (NOS) 44. This adapted version includes four domains of risk of bias assessment: methods for selecting study participants (selection bias), methods to control for confounding (performance bias), statistical methods (detection bias) and methods of exposure and outcome assessment (information bias).…”
Section: Methodsmentioning
confidence: 99%
“…Sex. It was important to include sex as a potential correlate because studies have shown that sex and gender may influence outcomes for OAT patients [41,42]. The sex variable was created from the RPDB database.…”
Section: Correlatesmentioning
confidence: 99%
“…158, 165 An adapted version of the Newcastle-Ottawa Scale was used to analyze the risk of bias in cross-sectional studies because a specific review tool is unavailable. 16 It has been used in previous systematic reviews. 101 This tool includes 4 risk of bias domains: i) selection bias (methods for selecting study participants), ii) performance bias (methods to control for confounding), iii) detection bias (statistical methods), and iv) information bias (methods of exposure and outcome assessment).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%